Existence of monotone equilibria in large double auctions - Paulo Barelli; Srihari Govindan (Theoretical Economics, 2024)
We provide a shorter proof of the main result in Reny and Perry (2006, Econometrica) by establishing a lower semicontinuity property of auctions as the number of traders goes to infinity, leveraging existence of equilibria in the limit auction. Our proof also eliminates two of the assumptions in their paper.
Keywords: C62; D44; D82; 330; degree theory; large auctions; Monotone equilibrium; rational expectations equilibrium